PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN STRATEGI PEMBELAJARAN INKUIRI DI KELAS IV - sari, lolita; zen, mulyani; ahmad, syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to describe the improvement of students’ learning outcomes in learning natural science by using inquiry learning strategy in the fourth grade. This was a classroom action research which applied qualitative and quantitative approaches. The subject of the research was teacher and 15 students. The students’ average score improve from 68,26 (adequate) in the first cycle into 76,49 (adequate) in the second cycle. It means the inquiry learning strategy successfully improves the students’ outcomes in learning natural science in the fourth grade of Elemantary School. Keywords : inquiry learning strategy